Myasthenic Syndromes – Impact of Rehabilitation and Sports - Henze, Thomas (Neurology International Open, 2018)
Patients suffering from disorders of neuromuscular transmission are only rarely admitted to rehabilitation facilities. However, patients suffering from severe muscular weakness of arms or legs, dysphagia, dysarthria, or respiratory insufficiency, especially after myasthenic crisis, will benefit from rehabilitation. Its goal is maximal reduction of existing disabilities that will enable participation in social life. Besides extensive knowledge of the clinical course and potential complications of myasthenic syndromes, a comprehensive rehabilitation concept is an important prerequisite for successful rehabilitation that includes individual and multimodal physical training as well as coping with the disease, public health medical aspects, education, and assistive devices.
Keywords: myasthenia gravis; myasthenic syndromes; rehabilitation; sports